A Review of the Role of Flavonoids in Peptic Ulcer (2010-2020) - Serafim, Catarina; Araruna, Maria Elaine; Junior, Edvaldo Alves; Diniz, Margareth; Hiruma-Lima, Clelia [UNESP]; Batista, Leonia (Mdpi, 2020)
Peptic ulcers are characterized by erosions on the mucosa of the gastrointestinal tract that may reach the muscle layer. Their etiology is multifactorial and occurs when the balance between offensive and protective factors of the mucosa is disturbed. Peptic ulcers represent a global health problem, affecting millions of people worldwide and showing high rates of recurrence. Helicobacter pylori infection and the use of non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most important predisposing factors for the development of peptic ulcers. Therefore, new approaches to complementary treatments are needed to prevent the development of ulcers and their recurrence. Natural products such as medicinal plants and their isolated compounds have been widely used in experimental models of peptic ulcers. Flavonoids are among the molecules of greatest interest in biological assays due to their anti-inflammatory and antioxidant properties. The present study is a literature review of flavonoids that have been reported to show peptic ulcer activity in experimental models. Studies published from January 2010 to January 2020 were selected from reference databases. This review refers to a collection of flavonoids with antiulcer activity in vivo and in vitro models.
Keywords: flavonoids; peptic ulcer; review